Analysis Of Student Cognitive Results Using The Team Games Tournament Model Integrated On The Ferris Wheel Media For Buffer Solution Subjects - Rizka Fahreza; Ayu Rahmi; Isna Rezkia Lukman; Marini Damanik; Eddiyanto Eddiyanto (Jurnal Siliwangi: Seri Pendidikan, 2021)
This study aims to determine the effect of the Teams Games Tournament (TGT) learning model using the Ferris wheel on students' cognitive learning outcomes on the buffer solution. The form of research is a quasi-experimental design using the posttest only design method with non-equivalent groups. The sampling technique used purposive sampling technique. The population in this study were all students of class XI Mathematics and Natural Sciences, State High School 1 Lhokseumawe Year 2019/2020, totaling 294 students. With a research sample of 50 students. Data collection methods in the form of observation, interviews, and tests. Before conducting the research, the questions that will be used are first tested to a school that is equivalent to the place of research. The questions tested are viewed in terms of the level of problem difficulty, discriminatory power, validity, reliability, to test distractors. The results showed that there was a significant difference in the Experiment I class and the Experiment II class. Cognitive, shown from the average of the experimental class I was 85.37 while the experimental class II was 79.58. Cognitive results sig. (2-tailed) t-test for equality of means on equal variances assumed is 0.008 according to the existing criteria if the value of sig 0.05 then Ha is accepted. It was concluded that the use of the TGT model using the Ferris wheel had a positive effect on student learning outcomes in the material for the buffer solution for class XI MIA SMA Negeri 1 Lhokseumawe.